Disciplines for and against Psychology - Burman, Erica; Manchester Metropolitan University (2012)
This paper evaluates the scope and functions of interdisciplinary connections for psychologists in dealing with its conceptual and methodological and sometimes political difficulties. Developing examples from my own context and practice, I indicate how feminist research has engaged with and addressed such questions. Brief consideration of three key epistemological turns in psychology, indicates that psychologists should neither uncritically turn to, nor turn away from, other disciplines but rather understand how what it is within such turns that indicates more about the nature of the conceptual, methodological and political problems we are trying to address.